In vitro evaluation of fluorocarbon leader line for use as a fabella-tibial suture - Banwell, M. N.; Hosgood, G.; Kerwin, S. C.; Hedlund, C. S.; Metcalf, J. B. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Cranial cruciate ligament rupture is a common injury in dogs, for which a variety of surgical techniques have been described. A commonly performed surgical technique is extracapsular stabilization with a lateral fabella-tibial suture (LFS) using large diameter nylon leader line (NLL). Inherent properties of NLL such as memory, low coefficient of friction, and large diameter may compromise knot security. Fluorocarbon (polyvinylidene fluoride; PVDF) has been investigated as a biomaterial for a variety of implants and is available as a high tensile strength fluorocarbon leader line (FCL). For a given tensile strength FCL is one-half the diameter of NLL. This study evaluated the force at failure, elongation, and stiffness of FCL compared to NLL for use as a LFS. The effects of steam and ethylene oxide sterilization on FCL were also evaluated. The results of this study demonstrate similar force at failure and stiffness for FCL when compared to NLL. In addition, the use of FCL may eliminate the elongation under low load observed with NLL. The mechanical properties of FCL loops were not affected by ethylene oxide sterilization. In contrast, steam sterilization caused significant detrimental effects on the mechanical properties of FCL and is not recommended. The reduced diameter and pliable feel of FCL allow for superior handling, formation of a less bulky and potentially more secure knot, and less foreign material in the region of implantation. FCL appears to be a suitable alternative material to NLL for a lateral fabella-tibial suture.
Keywords: Fluorocarbon; PVDF; Cranial cruciate ligament